2015
DOI: 10.15740/has/rjahds/6.1/37-40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of non-genetic factors on body weight traits of goats reared in hot humid climate

Abstract: : Growth is of great economic importance and requires particular attention for increasing total productivity in goat. The birth weight and early growth rate of animals are determined not only by genetic potential and also by maternal and environmental factors. Hence, an attempt has been made to know the effects of various non-genetic factors on the body weight at birth and different stages of growth. Data were collected from 180 goats belongs three genetic groups viz., Mablabari, Attappaddy and crossbred Malab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Rhind et al (1989) reported that in ewes with high BCS (more than 4.0) the primary embryo wastage increased and reproductive performance decreased. In beef cattle, BCS had an impact on fertility rates (Venkatachalapathy et al, 2015). Rhind et al (1989) showed that a BCS of more than 3.0 at mating caused low lamb production and the number of born lambs per ewe at mating was highest in the ewes with a BCS of 2.75.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…Rhind et al (1989) reported that in ewes with high BCS (more than 4.0) the primary embryo wastage increased and reproductive performance decreased. In beef cattle, BCS had an impact on fertility rates (Venkatachalapathy et al, 2015). Rhind et al (1989) showed that a BCS of more than 3.0 at mating caused low lamb production and the number of born lambs per ewe at mating was highest in the ewes with a BCS of 2.75.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%